Kriteria/Keadaan yang Bersifat Kasuistik dalam Penghentian Penuntutan Berdasarkan Keadilan Restoratif - Teza Salih Mauludin; Lies Sulistiani; Ajie Ramdan (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This legal research aims to examine the provisions of criteria/circumstances that are casuistic in the termination of prosecution based on restorative justice. Prosecutor's Regulation Number 15 of 2020 concerning the Termination of Prosecution Based on Restorative Justice mentions the provisions of a quo in Article 5 Paragraph (2) and Article 5 Paragraph (5). The a quo provision in the regulation does not have clear indicators so it is prone to multiple interpretations. The research method used is normative juridical by examining literature materials or secondary data. There are two approaches, namely the legislative approach and the case approach. Data collection techniques are also used interview techniques in the form of questions and answers with the Public Prosecutor of the District Attorney's Office to obtain information that supports this research. The results of the study show that there are no clear indicators of criteria/circumstances of a casuistic nature in the termination of prosecution based on restorative justice has implications for the results of the public prosecutor's decision to consider the application for Restorative Justice. The absence of explanation of the provision was returned to the consideration of the public prosecutor with discretionary authority.